∫ 0 1 ( 1 − x ln x ) 4 d x + 4 ∫ 0 1 ( 1 − x ln x ) 3 d x = c a π b ( π d − e )
where a , b , c , d , and e are positive integers. Find a + b + c + d + e .
Bonus: Find a general formula for ∫ 0 1 ( 1 − x ln x ) k d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Note that we have the expansion of the so-called "rising factorial" x ( n ) = j = 0 ∏ n − 1 ( x + j ) = j = 1 ∑ n [ j n ] x j n ≥ 1 where [ k n ] is an unsigned Stirling number of the first kind. Also note that ( 1 − x ) − k − 1 = r = 0 ∑ ∞ k ! ( r + 1 ) ( k ) x r ∣ x ∣ < 1 , k ≥ 1 while ∫ 0 1 x u ( ln x ) v d x = ( − 1 ) v + 1 ( u + 1 ) v + 1 v ! u , v ∈ N ∪ { 0 } Thus I k = ∫ 0 1 ( 1 − x ln x ) k + 1 d x = r = 0 ∑ ∞ k ! ( r + 1 ) ( k ) ∫ 0 1 x r ( ln x ) k + 1 d x = ( − 1 ) k + 1 r = 0 ∑ ∞ k ! ( r + 1 ) ( k ) × ( r + 1 ) k + 2 ( k + 1 ) ! = ( − 1 ) k + 1 ( k + 1 ) r = 0 ∑ ∞ ( r + 1 ) k + 2 ( r + 1 ) ( k ) = ( − 1 ) k + 1 ( k + 1 ) r = 0 ∑ ∞ ( r + 1 ) k + 2 1 j = 1 ∑ k [ j k ] ( r + 1 ) j = ( − 1 ) k + 1 ( k + 1 ) j = 1 ∑ k [ j k ] ζ ( k + 2 − j ) Thus I 2 I 3 = − 3 [ ζ ( 3 ) + ζ ( 2 ) ] = − 3 ζ ( 3 ) − 2 1 π 2 = 4 [ ζ ( 4 ) + 3 ζ ( 3 ) + ζ ( 2 ) ] = 4 5 4 π 4 + 1 2 ζ ( 3 ) + 3 2 π 2 and so the desired quantity is I 3 + 4 I 2 = 4 5 4 π 4 − 3 4 π 2 = 4 5 4 π 2 ( π 2 − 1 5 ) making the answer 4 + 2 + 4 5 + 2 + 1 5 = 6 8 .